Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a/\(\frac{1}{9}.3^4.3^n=3^7\)
\(\frac{1}{9}.81.3^n=3^7\)
\(\frac{81}{9}.3^n=3^7\)
\(9.3^n=3^7\)
\(3^2.3^n=3^7\)
\(3^2.3^n=3^2.3^5\)
vậy \(n=5\)
b/ \(\frac{1}{2}.2^n+4.2^n=9.2^5\)
\(2^n\left(\frac{1}{2}+4\right)=9.2^5\)
\(2^n.\frac{9}{2}=9.32\)
\(2^n.\frac{9}{2}=288\)
\(2^n=288:\frac{9}{2}\)
\(2^n=64\)
\(2^n=2^6\)
Vậy \(n=6\)
2^n.4=128
2^n=128:4
2^n=32
2^n=2^5
Suy ra n=5
3^n+1.9=81
3^n+1=81:9
3^n+1=9
3^n+1=3^2
Suy ra n=1
15^n-2=9^2:3^4
15^n-2=3^4:3^4
15^n-2=3^0
15^n-2=1
15^n-2=15^0
Suy ra n=2
co gi ko hieu thi hoi nha
a) 120 - 5 . ( x + 2 ) = 45
5 . (x + 2) = 120 - 45
5 . (x + 2) = 75
x + 2 = 75 : 5
x + 2 = 15
x = 17
b) ( 2.x - 3 )2 = 49
( 2.x - 3 )2 = 72
( 2.x - 3 ) = 7
2x = 10
x = 5
1, xy-2x+3y=9
<=> xy-2x+3y-9=0
<=> x(y-2) + 3(y-2)=0
<=>(y-2)(x+3)=0
<=>+) y-2=0 <=> y=2
+)x+3=0<=>x=-3
b) n + 3 \(⋮\) n - 1 <=> (n - 1) + 4 \(⋮\) n - 1
=> 4 \(⋮\) n - 1 (vì n - 1 \(⋮\) n - 1)
=> n - 1 ∈ Ư(4) = {±1; ±2; ±4}
Lập bảng giá trị:
n - 1 | 1 | -1 | 2 | -2 | 4 | -4 |
n | 2 | 0 | 3 | -1 | 5 | -3 |
Vậy n ∈ {2; 0; 3; -1; 5; -3}
a)Ta có : 3n + 1 = 917
<=> 3n + 1 = (32)17
<=> 3n + 1 = 334
<=> n + 1 = 34
<=> n = 33
Vậy n= 33
b)Ta có : 2n + 1 + 2n + 3 = 320
<=> 2n(2 + 23) = 320
<=> 2n . 10 = 320
<=> 2n = 32
<=> 2n = 25
<=> n = 5
Vậy n = 5
Ta có : 3n + 1 = 917
=> 3n + 1 = (32)17
=> 3n + 1 = 334
=> n + 1 = 34
=> n = 33
Ta có : 2n + 1 + 2n + 3 = 320
=> 2n(2 + 23) = 320
=> 2n . 10 = 320
=> 2n = 32
=> 2n = 25
=> n = 5
Vậy n = 5